Experimental Investigation into the Influences of Weathering on the Mechanical Properties of Sedimentary Rocks - Xiaoshuang Li; Yingchun Li; Saisai Wu (Geofluids)
The time-dependent behaviors of the sedimentary rocks which refer to the altering of the mechanical and deformable properties of rock elements in the long-term period are of increasing importance in the investigation of the failure mechanism of the rock strata in underground coal mines. In order to obtain the accurate and reliable mechanical parameters of the sedimentary rocks at different weathering grades, the extensive experimental programs including the Brazilian splitting test, uniaxial compression tests, and direct shear tests have been carried out on the specimens that exposed to the nature environments at different durations. The correlation between the weathering grades and mechanical parameters including uniaxial tensile strength, uniaxial compression strength, elastic modulus, Poisson’s ratio, cohesion, and friction coefficient was proposed. The obtained results suggested that uniaxial tensile strength, uniaxial compressive strength, elastic modulus, and cohesion dramatically decreased with increasing weathering time, characterized as the negative exponential relationship in general. The influences of various weathering grades on fracture behavior of the rock specimens were discussed. The cumulative damage of the rock by the weathering time decreased the friction coefficient of the specimens which led to the initiation and propagation of microcrack within the rock at lower stress conditions. The obtained results improved the understanding of the roles of weathering on the mechanical properties of sedimentary rocks, which is helpful in the design of the underground geotechnical structures.